Serine proteases of the complement system. (October 2000) - Sim, R. B.; Laich, A.
Abstract : The complement system in blood plasma is a major mediator of innate immune defence. The function of complement is to recognize, then opsonize or lyse, particulate materials, including bacteria, yeasts and other microrganisms, host cell debris and altered host cells. Recognition occurs by binding of complement proteins to charge or saccharide arrays. After recognition, a series of serine proteases is activated, culminating in the assembly of complex unstable proteases called C3/C5 convertases. These activate the complement protein C3, which acts as an opsonin. The complement serine proteases include the closely related Clr, Cls, MASPs 1–3 (80–90 kDa), C2 and Factor B (100 kDa), Factor D (25 kDa) and Factor 1 (85 kDa). Each of these has unusually restricted specificity and low enzymic activity. The C1r, C1s and MASP group occur as proenzymes. When activated, they are regulated, like many plasma serine proteases, by a serpin, C1-inhibitor. C2 and Factor B, however, have complex multiple regulation by a group of complement proteins called the Regulation of Complement Activation (or RCA) proteins, whereas Factors I and D appear to have no natural inhibitors. Advances in structure determination and protein-protein interaction properties are leading to a more detailed understanding of the complement-system proteases, and are indicating possible new routes for potential therapeutic control of complement.